Clinical stratification utility of HER2, PD-L1, MSI/MMR, and CLDN18.2 in conversion therapy for gastric cancer: narrative review - Tao Ding; Peiqiang Chen; Huajiong Yu (Frontiers in Oncology, 2026)
Most patients with gastric cancer considered for conversion therapy present with locally advanced or metastatic disease, where surgery alone or conventional chemotherapy often provides limited benefit. Conversion therapy aims to reduce tumor burden through systemic treatment, reassess treatment response over time, and create an opportunity for radical surgery with complete tumor removal. This approach is mainly considered for patients with initially unresectable, borderline resectable, or limited metastatic disease. However, because not all patients benefit from this strategy, careful selection of those most likely to respond to systemic therapy and proceed to surgery is essential. With the development of immunotherapy and targeted therapy, conversion therapy for gastric cancer has shifted from empiric chemotherapy toward biomarker-guided individualized treatment. HER2 status may guide anti-HER2 therapy, PD-L1 may help identify patients who benefit from immunotherapy combined with chemotherapy, MSI-H/dMMR suggests greater sensitivity to immunotherapy, and CLDN18.2 provides a new targeted option, particularly for HER2-negative disease. This review examines the clinical value of HER2, PD-L1, MSI/MMR, and CLDN18.2 in treatment selection, response prediction, repeated reassessment, and surgical timing. These biomarkers may help identify patients with treatment-sensitive disease who warrant surgical reassessment. However, because most supporting evidence is extrapolated from palliative/metastatic or perioperative trials, such evidence should not be interpreted as demonstrating improved conversion-surgery or R0-resection rates, pathological response, or postoperative disease-free survival in conversion-therapy populations; surgical eligibility remains dependent on comprehensive clinical and multidisciplinary assessment.